The Role of Strategic Management in Tourism Business Sustainability: A Case Study on Digital Economy-Based Tourist Destinations - Johni Eka Putra; Riri Cornelia; Hapsari Widayani; Anggi Oktaviani; Muhammad Aqshel Revinzky (Jurnal Informasi dan Teknologi, 2025)
This study explores the role of strategic management in supporting tourism business sustainability within digital economy-based destinations, focusing on Ciletuh-Palabuhanratu Geopark in West Java, Indonesia. The research aims to determine whether differences in the level of digital-based strategic management among tourism actors influence their sustainability performance. Using a quantitative approach, data were collected from 90 respondents categorized into three groups: low, moderate, and high digital strategy adopters. A one-way ANOVA test was conducted to examine whether significant differences existed in the economic, social, and environmental dimensions of sustainability among the groups. The results show a statistically significant difference in sustainability outcomes, with businesses in the "high" digital strategy group demonstrating the most favorable performance. Economic sustainability emerged as the most impacted dimension, driven by better revenue growth and operational efficiency. Social and environmental dimensions also improved through increased community engagement, visitor satisfaction, and adoption of eco-friendly practices. These findings indicate that digital-based strategic management not only enhances competitiveness but also strengthens long-term sustainability. The study further highlights the importance of stakeholder collaboration in maximizing the effectiveness of digital strategies. Strategic alignment between tourism actors, local government, and communities is essential to build inclusive and resilient destination ecosystems. By integrating strategic planning with digital innovation, tourism businesses can achieve sustainability that is both profitable and responsible. The results contribute to the growing discourse on digital transformation in tourism and offer practical insights for policymakers, tourism managers, and local stakeholders in digitally emerging destinations.